1980
DOI: 10.1111/j.1600-0560.1980.tb00972.x
|View full text |Cite
|
Sign up to set email alerts
|

Urbach‐Wiethe Disease

Abstract: A case of lipoid proteinosis was subjected to clinical, histologic and electron microscopic study. Palpebral biopsies showed a large dermal infiltration composed of closely interwoven granulo-filamentous material in the superficial and deep dermis. Collagen fibers were normal. Fibroblasts seemed to play an active role in the synthesis of this accumulating substance. Around the dermal capillaries there was a prominent concentric multilamination of the basal lamina which was considered a reaction of the endothel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0
1

Year Published

1982
1982
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 0 publications
0
12
0
1
Order By: Relevance
“…Clinically patients have tlesh-colored papules, verrucotis nodules, and plaques involving the skin, predominantly on the face and on areas associated with mechanical trauma. The tongue, epiglottis, and vocal cords frequently show early tissue infiltration and the voice in almost all patients is hoarse from birth, infancy, or the first years of life, Intracranial calcifications, seizures, eye abnormalities, and parotitis can also be present (1,2). We report an 8-year-old boy affected by this syndrome and describe the cutaneous anomalies that were present in his mother.…”
mentioning
confidence: 88%
“…Clinically patients have tlesh-colored papules, verrucotis nodules, and plaques involving the skin, predominantly on the face and on areas associated with mechanical trauma. The tongue, epiglottis, and vocal cords frequently show early tissue infiltration and the voice in almost all patients is hoarse from birth, infancy, or the first years of life, Intracranial calcifications, seizures, eye abnormalities, and parotitis can also be present (1,2). We report an 8-year-old boy affected by this syndrome and describe the cutaneous anomalies that were present in his mother.…”
mentioning
confidence: 88%
“…O diagnóstico é confirmado através de biópsia cutânea. O exame histopatológico evidencia espessamento da derme com extensos depósitos de material hialino homogêneo extracelular PAS positivos e diástase-resistentes, caracterizados por acantose, hiperqueratose e paraqueratose da pele (5,21) . A Não houve alteração no eletroencefalograma.…”
Section: As Principais Manifestações Clínicas Encontradas Sãounclassified
“…Many electron microscopic studies of hyalinosis cutis et mucosae have revealed an abnormal accumulation of amorphous, fibrogranular mate rials accompanied by a remarkable multiplication of basal lamina around blood vessels and at the dermoepidermal junction [3,5,11]. In addition, the same changes around smooth muscle cells were first detected in tunica dartos with the electron microscope and described in the author's previous work [8,9], Hashimoto and others [5] proposed that hyalin in this disease was produced by abnormal fibroblasts which showed the presence of halfdesmosome-like structures being definitely rare in normal postnatal skin fibroblasts.…”
Section: Discussionmentioning
confidence: 99%